Free drugs for children! A study on fully subsidized prescription drugs for 17-year-olds in Sweden - Lund,Emma (2019)
This paper explores the effects of co-payment price reduction to zero for prescribed pharmaceuticals on the volume of medicine consumed and the price elasticity for youths. Data was collected from two Swedish national registries on pharmaceutical consumption and municipality socioeconomic factors for groups of ages 17 and 19, from January 2013 to June 2018. I use a difference-in-difference strategy to exploit the exogenous drop in January 2016 of medicine price for minors and if it differs between socioeconomic groups. The results show an association between zero price co-payment and increase of prescription drug use. Individuals living in high income municipalities increased their medical consumption with 15.2% while individuals living in low income municipalities increased their consumption with 14.5% due to the free drug reform. The price elasticity is greater for individuals living in high income municipalities, -0.120, than living in low income municipalities -0.110.
Keywords: pharmaceuticals; co-payment; zero price; price elasticity; average price elasticity